A New Method for Investigating Relationships Between Distribution of Sessile Organisms and Multiple Terrain Variables by Photogrammetry of Subtidal Bedrocks - Kanki, Takayuki; Nakamoto, Kenta; Hayakawa, Jun; Kitagawa, Takashi; Kawamura, Tomohiko (Frontiers in Marine Science, 2021)
Previous studies of habitat suitability of sessile organisms on subtidal rocky substrata have been focused only one or two terrain attributes. In this study, we propose a new method to construct a centimeter resolution seafloor topographic model by using underwater photogrammetry to obtain multiple terrain variables and to investigate relationships between the distribution of sessile organisms and multiple terrain variables. Point cloud models of five square sections (11.3–25.5 m2) of the bedrock surface of Otsuchi Bay were reconstructed with a 0.05 m resolution. Using the 0.01 m resolution point cloud models, five terrain variables were calculated on each face of the mesh models: height above seafloor, topological position index, slope, aspect, and ruggedness. The presence/absence data of four species of sessile organisms (ascidian Halocynthia roretzi, barnacle Balanus trigonus, polychaete Paradexiospira nakamurai, and articulated coralline algae Pachyarthron cretaceum) were located on the mesh models. H. roretzi and B. trigonus were more abundant on vertical and high faces above the seafloor, and P. nakamurai were more abundant at high faces above the surroundings. In high position where the current velocity increases, the three sessile animals may have an advantage for their suspension feeding. In contrast, P. cretaceum, unlike the other three sessile animal species, occurred at various heights and on gentle slope faces suitable for photosynthesis.